Robot City Guide to robots - Collicutt, Paul (London : Templar Publishing, 2011)
This novelty-packed guide showcases Robot City's biggest and best inhabitants in all their glory. Living in harmony with humanity, robots in the metal metropolis tackle all kinds of jobs. Meet Curtis the Colossal Coastguard-Robot, ro-boxers Smash Harry and Smokin' Jones, Massimo the Giant-Pizza-Delivery-Robot and the dancing Automettes, plus many other remarkable characters. Their fascinating functions, made clear with engaging text and accessible diagrams, explain simple mechanics and other concepts from Key Stage 1-3 science.
Keywords: Engineering - Robotics